The late Pleistocene origin of the Italian and Maltese populations of Potamon fluviatile (Malacostraca: Decapoda): insights from an expanded sampling of molecular data. Issue 1 (1st January 2017) - Vecchioni, L.; Deidun, A.; Sciberras, J.; Sciberras, A.; Marrone, F.; Arculeo, M.
Abstract: Evidence available for most inland water and terrestrial organisms highlights the significant role played by southern Italy, Sicily and the Maltese islands as refuges during Pleistocene climatic fluctuations. However, to date, the hypothesis that these areas may have acted as Pleistocene refugia for the freshwater crab Potamon fluviatile has not been explicitly tested, and a recent origin of local P. fluviatile populations was proposed on the basis of a small set of analysed molecular data. We have thus expanded the currently available data set on the population genetic structure of P. fluviatile through dedicated samplings in Sicily (Italy, 18 specimens), the Maltese Islands (Malta, 15 specimens) and the island of Corfu (Greece, seven specimens), with the explicit aim of testing the role of southern Italy, Sicily and the Maltese archipelago as refugia where early Pleistocene or pre-Quaternary populations of the freshwater crab could have persisted to date. Based on the analysis of both novel and published cytochrome c oxidase subunit I (COI) sequence data, we gathered evidence supporting a recent origin of the southern Italian, Sicilian and Maltese populations of Potamon fluviatile from the Balkans, thus rejecting the hypothesised Pleistocene persistence in the area of pre-existing local populations of the same species.